COMplot, A Graphical Presentation of Complication Profiles and Adverse Effects for the Curative Treatment of Gastric Cancer: A Systematic Review and Meta-Analysis - van den Ende, Tom; Abe Nijenhuis, Frank A.; van den Boorn, Héctor G.; ter Veer, Emil; Hulshof, Maarten C. C. M.; Gisbertz, Suzanne S.; van Oijen, Martijn G. H.; van Laarhoven, Hanneke W. M. (Frontiers in Oncology, 2019)
Background For the curative treatment of gastric cancer, several neoadjuvant and adjuvant treatment-regimens are available which have shown to improve overall survival. No overview is available regarding toxicity and surgery related outcomes aim was to construct a novel graphical method concerning adverse events (AEs) associated with multimodality treatment and perform a meta-analysis to compare different clinically relevant cytotoxic regimens with each other. Methods The PubMed, EMBASE, CENTRAL and ASCO/ESMO databases were searched up to May 2019 for randomized controlled trials investigating curative treatment regimens for gastric cancer. To construct single and bidirectional bar-charts (COMplots), grade 1-2 and grade 3-5 AEs were extracted per cytotoxic regimen. For surgery-related outcomes a pre-specified set of complications was used. Thereafter, treatment-arms comparing the same regimens were combined in a single-arm random-effects meta-analysis and pooled-proportions were calculated with 95% confidence-intervals. Comparative meta-analyses were performed based on clinical relevance and compound similarity. Results In total 16 RCTs (n= 4,526 patients) were included investigating preoperative-therapy and 39 RCTs investigating adjuvant-therapy (n=13,732 patients). Preoperative COMplots were created for among others; 5-fluorouracil/leucovorin-oxaliplatin-docetaxel (FLOT), epirubicin-cisplatin-fluoropyrimidine (ECF), cisplatin-fluoropyrimidine (CF) and oxaliplatin-fluoropyrimidine (FOx). Preoperative FLOT showed a minor increase in grade 1-2 and grade 3-4 AEs compared to preoperative ECF, CF and FOx. A pooled analysis of patients who had received preoperative therapy compared to patients who underwent direct surgery did not reveal any significant difference in surgery related morbidity/mortality. When we compared three commonly used adjuvant regimens; S-1 had the lowest amount of grade 3-4 AEs compared to capecitabine with oxaliplatin (CAPOX) and 5-FU with radiotherapy (5-FU+RT). Conclusion COMplot provides a novel tool to visualize and compare treatment related AEs for gastric cancer. Based on our comparisons, preoperative FLOT had a manageable toxicity profile compared to other preoperative doublet or triplet regimens. We found no evidence indicating surgical outcomes might be hampered by preoperative therapy. Adjuvant S-1 had a more favorable toxicity profile compared to CAPOX and 5-FU+RT.